Proposing prognostic thresholds for lymph node yield in clinically lymph node‐negative and lymph node‐positive cancers of the oral cavity. Issue 23 (1st August 2016) - Kuo, Phoebe; Mehra, Saral; Sosa, Julie A.; Roman, Sanziana A.; Husain, Zain A.; Burtness, Barbara A.; Tate, Janet P.; Yarbrough, Wendell G.; Judson, Benjamin L.
Abstract : BACKGROUND: Prognostic lymph node yield thresholds have been identified and incorporated into treatment guidelines for multiple cancer sites, but not for oral cancer. The objective of this study was to identify optimal thresholds in elective and therapeutic neck dissection for oral cavity cancers. METHODS: Patients with oral cavity cancers in the National Cancer Database (NCDB) were stratified into clinically lymph node‐negative (cN0) and clinically lymph node‐positive (cN+) cohorts to reflect the differing surgical management for these diseases. Univariate and multivariate analyses were performed to assess the relation between lymph node yield and overall survival, adjusting for other prognostic factors. Thresholds derived from the NCDB were validated in the Surveillance, Epidemiology, and End Results database. RESULTS: In patients with cN0 cancers of the oral cavity from the NCDB, those who had <16 lymph nodes had significantly decreased survival. The proportion of positive lymph nodes was higher for patients who had ≥16 lymph nodes (27.2% vs 16.3% for < 16 lymph nodes; P  < .001). This threshold was validated in 2715 lymph node‐negative cancers from SEER, with a mortality hazard ratio of 0.825 for ≥ 16 lymph nodes (95% confidence interval, 0.764‐0.950; P  = .004). In patients with cN + oral cavity cancers from the NCDB, groups with <26 lymph nodes had significantly decreased survival. This threshold was validated in 1903 lymph node‐positive cancers from SEER, with a mortality hazard ratio of 0.791 (95% confidence interval, 0.692‐0.903; P  = .001). Academic centers, higher volume centers, and geographic location predicted higher lymph node yields. CONCLUSIONS: More extensive neck dissection (≥16 lymph nodes in cN0,  ≥ 26 lymph nodes in cN+) was associated with better survival. Further evaluation of practice patterns in lymph node yield may represent an opportunity for improved quality of care. Cancer 2016;122:3624‐31. © 2016 American Cancer Society . Abstract : Prognostic thresholds for lymph node yield from neck dissection for cancers of the oral cavity are identified in the National Cancer Database and validated in the Surveillance, Epidemiology, and End Results database. More extensive neck dissection (yields of ≥ 16 lymph nodes in clinically lymph node‐negative cancers and ≥ 26 lymph nodes in clinically lymph node‐positive cancers) is associated with better survival.